Early treatment of complex located pediatric low‐grade gliomas using iodine‐125 brachytherapy alone or in combination with microsurgery. (29th December 2015) - Kunz, Mathias; Nachbichler, Silke B.; Ertl, Lorenz; Fesl, Gunther; Egensperger, Rupert; Niyazi, Maximilian; Schmid, Irene; Tonn, Joerg Christian; Peraud, Aurelia; Kreth, Friedrich Wilhelm
Abstract: To analyze efficacy, functional outcome, and treatment toxicity of low‐dose rate I‐125 brachytherapy (SBT) alone or in combination with best safe resection (in case of larger tumor volumes) as first‐line treatment for pediatric low‐grade gliomas (PLGGs) not suitable for complete resection. Consecutively treated (2000–2014) complex located circumscribed WHO grade I/II PLGGs were included. For small tumors (≤4 cm in diameter) SBT alone was performed; for larger tumors best safe resection and subsequent SBT was chosen. Temporary Iodine‐125 seeds were used (median reference dose: 54 Gy). Treatment response was estimated with the modified MacDonald criteria. Analysis of functional outcome included ophthalmological, endocrinological and neurological evaluation. Survival was analyzed with the Kaplan–Meier method. Prognostic factors were obtained from proportional hazards models. Toxicity was categorized according to the Common Terminology Criteria for Adverse Events. Fifty‐eight patients were included treated either with SBT alone ( n  = 39) or with SBT plus microsurgery ( n  = 19). Five‐year progression‐free survival was 87%. Two patients had died due to tumor progression. Among survivors, improvement/stabilization/deterioration of functional deficits was seen in 20/14/5 patients, respectively. Complete/partial response had beneficial impact on functional scores ( P  = 0.02). The 5‐year estimated risk to receive adjuvant radiotherapy/chemotherapy was 5.2%. The overall early (delayed) toxicity rate was 8.6% (10.3%), respectively. No permanent morbidity occurred. In complex located PLGGs, early SBT alone or combined with best safe resection preserves/improves functional scores and results in tumor control rates usually achieved with complete resection. Long‐term analysis is necessary for confirmation of these results. Abstract : In complex located PLGGs, early SBT alone or combined with best safe resection preserves/improves functional scores and results in tumor control rates usually achieved with complete resection. Long‐term analysis is necessary for confirmation of these results.